Pengaruh Work Life Balance, Reward dan Punishment Terhadap Kinerja Karyawan pada Bank Syariah Indonesia KCP Payakumbuh - Silvia, Wahyuni; Zuripal, Zuripal (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this research is to determine the effect of Work Life Balance, Reward, and Punishment on Employee Performance at Bank Syariah Indonesia KCP Payakumbuh. The method used is a survey. Data collection in this research employs a questionnaire distributed to all respondents. The analysis technique used is classical assumption testing, multiple linear regression, and hypothesis testing. The sample in this study is a census which includes the entire population of 40 employees of Bank Syariah Indonesia KCP Payakumbuh. The results of the research show that work-life balance has a significant positive effect on employee performance at Bank Syariah Indonesia KCP Payakumbuh. Rewards have a significant positive effect on employee performance at Bank Syariah Indonesia KCP Payakumbuh. Punishment has a significant positive effect on employee performance at Bank Syariah Indonesia KCP Payakumbuh.